CATALYST, METHOD FOR PRODUCING CATALYST, AIR ELECTRODE, AND AIR BATTERY

A two-step heat treatment and acid washing process creates a core-shell structured catalyst with nitrogen-containing transition metal complexes, addressing the catalytic limitations of existing carbon catalysts in metal-air secondary batteries by enhancing oxygen reduction and generation capabilities.

JP7605427B2Active Publication Date: 2024-12-24SHARP KK +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020146028
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-31
Publication Date
2024-12-24
Estimated Expiration
2040-08-31

AI Technical Summary

Technical Problem

Existing carbon catalysts for metal-air secondary batteries lack sufficient catalytic activity for both oxygen reduction and generation, limiting their use as positive electrodes.

Method used

A two-step heat treatment process involving a first and second inert gas atmosphere, combined with an acid washing step, is used to produce a catalyst with a core-shell structure, utilizing nitrogen-containing transition metal complexes to enhance catalytic abilities.

Benefits of technology

The resulting catalyst exhibits excellent catalytic performance for both oxygen reduction and generation, improving the functionality of air electrodes and air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605427000006
    Figure 0007605427000006
  • Figure 0007605427000007
    Figure 0007605427000007
  • Figure 0007605427000008
    Figure 0007605427000008
Patent Text Reader

Abstract

To provide a method for producing a catalyst having excellent catalysis of both oxygen reduction and oxygen generation.SOLUTION: A method for producing a catalyst includes a first heat treatment step and a second heat treatment step. In the first heat treatment step, a first nitrogen-containing transition metal complex and a carbon material are heated in a first inert gas atmosphere (S1). In the second heat treatment step, the carbon material resulting from the first heat treatment step and a second nitrogen-containing transition metal complex are heated in a second inert gas atmosphere (S2).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst, a method for producing the catalyst, an air electrode including the catalyst, and an air battery including the air electrode. [Background technology]

[0002] Conventionally, electrode catalysts used in metal-air batteries have been made of particles of precious metals such as platinum, or particles of precious metals such as platinum supported on a single carbon material such as carbon black. Precious metals such as platinum exhibit high catalytic activity and activity stability.

[0003] On the other hand, precious metals such as platinum are very expensive and resources are limited. In recent years, alternative catalysts that use less or no precious metals have been proposed, and various electrode catalysts made of inexpensive materials have also been proposed.

[0004] For example, Patent Documents 1 and 2 disclose carbon catalysts obtained by heat treating one or more organic dyes selected from macrocyclic compounds such as phthalocyanine and porphyrin that do not contain precious metal elements. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-158674 A [Patent Document 2] JP 2012-110811 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, when the carbon catalysts disclosed in Patent Documents 1 and 2 were used in the air electrode of a metal-air secondary battery, they did not exhibit sufficient catalytic activity as an oxygen generating catalyst, and the air electrode could not be used as a positive electrode for charging.

[0007] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a catalyst that does not use a precious metal such as platinum and that is endowed with excellent catalytic capabilities for both oxygen reduction and oxygen generation, a method for producing the catalyst, and to provide an air electrode and an air battery that include the catalyst. [Means for solving the problem]

[0008] In order to achieve the above-mentioned object, the method for producing a catalyst according to the present disclosure is characterized by including a first heat treatment step of heating a carbon material and a first nitrogen-containing transition metal complex in a first inert gas atmosphere, and a second heat treatment step of heating the carbon material that has been subjected to the first heat treatment step and a second nitrogen-containing transition metal complex in a second inert gas atmosphere.

[0009] In the method for producing the catalyst having the above configuration, it is preferable to further include an acid washing step after the second heat treatment step, and it is also preferable to further include a temperature lowering step between the first heat treatment step and the second heat treatment step.

[0010] In the above-mentioned method for producing a catalyst, more specifically, it is preferable that the calcination temperature in the first heat treatment step is 800 to 1200°C, and the calcination temperature in the second heat treatment step is 600 to 1200°C.

[0011] Moreover, the firing temperature in the first heat treatment step is preferably higher than the firing temperature in the second heat treatment step.

[0012] By satisfying the above-mentioned specific features, it is possible to produce a catalyst that is endowed with excellent catalytic ability for both oxygen reduction and oxygen generation. The produced catalyst can be suitably used for the positive electrode (air electrode) of a metal-air secondary battery.

[0013] The catalyst manufactured by the manufacturing method of the above configuration is also within the scope of the technical idea of ​​the present invention. That is, the catalyst in the present disclosure is characterized by having a carbon material, fine particles containing a metal or metal carbide supported on the surface of the carbon material, and a shell layer covering the surface of the fine particles. In addition, an air electrode containing the catalyst and an air battery including the air electrode are also within the scope of the technical idea of ​​the present invention. Effect of the Invention

[0014] According to the present invention, it is possible to produce a catalyst that is endowed with excellent catalytic ability for both oxygen reduction and oxygen generation, and the catalyst can be used to provide an air electrode and an air battery with improved cell performance. [Brief description of the drawings]

[0015] [Figure 1] 1 is a flowchart illustrating an outline of steps in a method for producing a catalyst according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is an explanatory view showing a state before a first heat treatment step in the production method of the catalyst according to the first embodiment of the present disclosure. [Diagram 3] FIG. 2 is an explanatory view showing a state after a first heat treatment step in the production method of the catalyst. [Figure 4] FIG. 2 is an explanatory view showing a state after a first heat treatment step and before a second heat treatment step in the production method of the catalyst. [Diagram 5] FIG. 2 is an explanatory view showing an example of the obtained catalyst after a second heat treatment step in the production method of the catalyst. [Figure 6] FIG. 4 is an explanatory view showing another example of the obtained catalyst after the second heat treatment step in the production method of the catalyst. [Figure 7] FIG. 11 is an explanatory view showing an example of an obtained catalyst after a second heat treatment step in a production method of a catalyst according to a second embodiment of the present disclosure. [Figure 8] FIG. 4 is an explanatory view showing another example of the obtained catalyst after the second heat treatment step in the production method of the catalyst. [Figure 9]1 is a graph showing the relationship between oxygen reduction current and electrode potential in examples and comparative examples according to an embodiment of the present disclosure. [Figure 10] 1 is a graph showing the relationship between oxygen generating current and electrode potential in examples and comparative examples according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] A metal-air battery is a battery that is composed of an air electrode, a fuel electrode, an electrolyte, etc., and extracts electrical energy obtained in the process in which the metal used as fuel (hereinafter referred to as the fuel metal) changes into a metal oxide through an electrochemical reaction. For example, if the fuel metal is zinc, zinc reacts with hydroxide ions at the fuel electrode during discharge, producing zinc hydroxide and releasing electrons. The released electrons flow to the air electrode, and the resulting current becomes the output of the battery. Zinc hydroxide is further decomposed into zinc oxide and water, and the water returns to the electrolyte.

[0017] During discharge, oxygen in the air and electrons received from the fuel electrode react with water (oxygen reduction reaction) at the air electrode, resulting in hydroxide ions. These hydroxide ions travel ionically through the electrolyte and reach the fuel electrode. This cycle utilizes oxygen taken in from the air electrode and zinc as fuel, allowing continuous power generation while zinc oxide is formed.

[0018] In such metal-air batteries, a catalyst (oxygen reduction catalyst) is used in the air electrode to further activate the oxygen reduction reaction.

[0019] Furthermore, in a metal-air secondary battery, if the air electrode is used as the positive electrode during charging, a reaction occurs at the air electrode during charging that is the opposite of that during discharging (a reaction that produces oxygen, water, and electrons from hydroxide ions: oxygen evolution reaction). In this case, the catalyst used at the air electrode is required to function not only as an oxygen reduction catalyst required during discharging, but also as an oxygen evolution catalyst required during charging.

[0020] (Catalyst manufacturing method) The method for producing a catalyst (carbon catalyst) in the present disclosure is applied to the production of a catalyst used in the positive electrode (air electrode) of a metal-air secondary battery, and can impart a function as an oxygen generating catalyst to the produced catalyst. Furthermore, as shown in FIG. 1, the method for producing a catalyst in the present disclosure roughly includes the following steps.

[0021] First heat treatment step (S1): The first nitrogen-containing transition metal complex and the carbon material are heated in a first inert gas atmosphere. The preferred firing temperature (heating temperature) in this step is 800 to 1200°C.

[0022] Second heat treatment step (S2): The carbon material obtained in the first heat treatment step and the second nitrogen-containing transition metal complex are heated in a second inert gas atmosphere. The preferred firing temperature (heating temperature) in this step is 600 to 1200°C.

[0023] Acid washing step (S3): The carbon material obtained in the second heat treatment step is washed with acid.

[0024] This manufacturing method includes two heat treatment steps, a first heat treatment step and a second heat treatment step. These first and second heat treatment steps are steps for forming a catalyst having a core-shell structure, more specifically, the first heat treatment step is a step for forming a core, and the second heat treatment step is a step for forming a shell layer. The acid washing step is a step for removing metal components that are not covered by the shell layer from the carbon material that has been subjected to the second heat treatment step.

[0025] The order of each step from the first heat treatment step to the acid washing step cannot be changed. However, the method for producing a catalyst according to the present disclosure is not limited to a method in which only the first heat treatment step, the second heat treatment step, and the acid washing step are performed. For example, other steps such as a step of lowering the temperature may be included between the first heat treatment step and the second heat treatment step.

[0026] At least one of the first nitrogen-containing transition metal complex and the second nitrogen-containing transition metal complex is preferably a macrocyclic compound (a general term for organic compounds having a cyclic molecular structure in which the number of atoms constituting the ring is approximately 10 or more). Both the first nitrogen-containing transition metal complex and the second nitrogen-containing transition metal complex may be macrocyclic compounds.

[0027] The first nitrogen-containing transition metal complex may have various variations depending on the combination of the central metal species and the complex species. The first nitrogen-containing transition metal complex is represented by the following general formula (I).

[0028] M1·L1 …(I) In general formula (I), M1 represents the first central metal of the first nitrogen-containing transition metal complex, and L1 represents the first cyclic ligand that is coordinated to the first central metal M1 and has a nitrogen-containing cyclic ligand structure of the first nitrogen-containing transition metal complex. The first cyclic ligand L1 is coordinated to the first central metal M1 when some of the atoms constituting the ring of the first cyclic ligand L1 donate an electron pair to the first central metal M1, and a coordinate bond is formed between some of the atoms constituting the ring of the first cyclic ligand L1 and the first central metal M1.

[0029] The first central metal M1 represents an element belonging to Groups 3 to 11 of the periodic table, and for example, at least one element selected from the group consisting of Sc, Y, La, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Ru, Co, Ni, Pd, Cu, Ag and Au is preferred. Among them, at least one element selected from the group consisting of Nb, Cr, Mn, Fe, Ru, Co, Ni, Pd and Cu is more preferred, and at least one element selected from the group consisting of Fe and Co is particularly preferred. When the first central metal M1 is Fe, the catalyst produced by the catalyst production method of the present disclosure has the highest activity in the oxygen reduction reaction and the oxygen evolution reaction.

[0030] The first cyclic ligand L1 may be a monodentate ligand in which one atom constituting the ring of the first cyclic ligand L1 is coordinated to the first central metal M1, or may be a multidentate ligand in which two or more atoms constituting the ring of the first cyclic ligand L1 are coordinated to the first central metal M1. The number of coordination sites of the first cyclic ligand L1 is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more.

[0031] Specifically, the first cyclic ligand L1 preferably has a chemical structure including at least one skeleton selected from those represented by the following general formulas (II) to (IX).

[0032] [ka]

[0033] The above general formula (II) represents a porphyrin skeleton. 1 ~A 4 are the same or different and each represents a nitrogen atom or a carbon atom, and the carbon atom may be bonded to a monovalent substituent. 1 ~A 4 At least one of A is preferably a nitrogen atom; 1 ~A 4 More preferably, each of represents a nitrogen atom.

[0034] [ka]

[0035] The above general formula (III) represents a phthalocyanine skeleton. The above general formula (IV) represents a porphycene skeleton. The above general formula (V) represents a corrphycene skeleton. The above general formula (VI) represents a hemiporphycene skeleton. The above general formula (VII) represents a corrole skeleton. The above general formula (VIII) represents an azacorrole skeleton. The above general formula (IX) represents a cyclam skeleton.

[0036] More specifically, when the first nitrogen-containing transition metal complex has the phthalocyanine skeleton shown in the above general formula (III), it is more preferably represented by the following general formula (X).

[0037] [ka]

[0038] In the above general formula (X), X 1 ~X 8 are the same or different and each represents a hydrogen atom or a monovalent substituent. D 1 ~D 8 are the same or different and represent a nitrogen atom or a carbon atom, and a hydrogen atom or a monovalent substituent is bonded to the carbon atom. A solid line between a nitrogen atom and an iron atom represents a covalent bond between the nitrogen atom and the iron atom. A dashed line between a nitrogen atom and an iron atom represents a coordination of the nitrogen atom to the iron atom. 1 ~D 8 More preferably, each of X represents a carbon atom. 1 ~X 8 are each a hydrogen atom, the catalyst produced by the production method for a catalyst (carbon catalyst) according to the present disclosure can exhibit more remarkable catalytic abilities for both oxygen reduction and oxygen generation.

[0039] The second nitrogen-containing transition metal complex may have various variations depending on the combination of the central metal species and the complex species. The second nitrogen-containing transition metal complex is represented by the following general formula (XI).

[0040] M2·L2 …(XI) In general formula (XI), M2 represents the second central metal of the second nitrogen-containing transition metal complex, and L2 represents a second cyclic ligand that is coordinated to the second central metal M2 and has a nitrogen-containing cyclic ligand structure of the second nitrogen-containing transition metal complex. The second cyclic ligand L2 is coordinated to the second central metal M2 when some of the atoms constituting the ring of the second cyclic ligand L2 donate an electron pair to the second central metal M2, forming a coordinate bond between some of the atoms constituting the ring of the second cyclic ligand L2 and the second central metal M2.

[0041] The second central metal M2, like the first central metal M1, represents an element belonging to Groups 3 to 11 of the periodic table, and suitable examples thereof include at least one element selected from the group consisting of Sc, Y, La, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Ru, Co, Ni, Pd, Cu, Ag, and Au. It is more preferable that the second central metal M2 is the same element as the first central metal M1.

[0042] The second cyclic ligand L2 preferably contains at least one selected from the same cyclic ligands as the first cyclic ligand L1. The second cyclic ligand L2 preferably has a chemical structure containing at least one selected from the skeletons represented by the above general formulas (II) to (IX), similar to the first cyclic ligand L1.

[0043] In the acid washing step, the carbon material obtained in the second heat treatment step is acid washed. When the catalyst is made into an electrode to construct an air battery, there is a risk that the metal parts not covered by the shell layer will dissolve in the air battery and become a source of hydrogen generation at the negative electrode, inhibiting the electrode reaction. In this manufacturing method, the acid washing step is further included after the second heat treatment step, making it possible to prevent such problems from occurring. [First embodiment] In the first embodiment, each step in the method for producing a catalyst according to the present disclosure will be described in detail, taking as an example a case in which the first nitrogen-containing transition metal complex and the second nitrogen-containing transition metal complex are both iron phthalocyanine.

[0044] Figures 2 to 5 show a method for producing a catalyst in embodiment 1, where Figure 2 is an explanatory diagram showing the state before the first heat treatment step, Figure 3 is an explanatory diagram showing the state after the first heat treatment step, Figure 4 is an explanatory diagram showing the state after the first heat treatment step and before the second heat treatment step, and Figure 5 is an explanatory diagram showing the state after the second heat treatment step.

[0045] As shown in Fig. 2, in the first heat treatment step in this production method, a first nitrogen-containing transition metal complex 11 and a carbon material 12 are heated in a first inert gas atmosphere. The first nitrogen-containing transition metal complex 11 is an iron phthalocyanine having an Fe central metal. The first inert gas is preferably, for example, Ar (argon) or Xe (xenon). The firing temperature in the first heat treatment step is preferably 800 to 1200°C.

[0046] In the first heat treatment step, the first nitrogen-containing transition metal complex 11 is sublimated. Then, as shown in Fig. 3, cores 13 of particles (iron-containing particles) containing mainly Fe, the central metal of the first nitrogen-containing transition metal complex 11, are formed (aggregated Fe, core formation). Cores (aggregated Fe) 13 are attached to the surface of the carbon material 12.

[0047] If the firing temperature in the first heat treatment step is too low, the aggregation of Fe does not proceed, and a scaffold for forming a shell in the second heat treatment step cannot be formed. If the firing temperature in the first heat treatment step is too high, the aggregation of Fe proceeds too much, the surface area of ​​the shell layer 15 formed on the core 13 described later decreases, and the reactive active points decrease. Therefore, the firing temperature in the first heat treatment step is preferably set to 800 to 1200°C.

[0048] 4, in the second heat treatment step in the present production method, the second nitrogen-containing transition metal complex 14 and the carbon material 12 having the core 13 obtained in the first heat treatment step are heated in a second inert gas atmosphere. The second nitrogen-containing transition metal complex 14 is an iron phthalocyanine having Fe as the central metal. The second inert gas is preferably, for example, Ar (argon).

[0049] 5, a shell layer 15 can be formed (shell formation) on the surface of the core 13. The second nitrogen-containing transition metal complex 14 may be the same as or different from the first nitrogen-containing transition metal complex 11.

[0050] The calcination temperature in the second heat treatment step in the present manufacturing method is sufficient as long as the phthalocyanine of the second nitrogen-containing transition metal complex 14 is sublimated, and can be a relatively low calcination temperature of 600 to 1200°C. The first heat treatment step is, for example, a step of sublimating iron phthalocyanine to form the core 13, which is an iron-containing particle, and requires a higher calcination temperature than the second heat treatment step. On the other hand, the second heat treatment step is a step of forming the shell layer 15, which is an iron-containing carbon thin film, on the core (aggregated Fe) 13 (shell formation). Therefore, the calcination temperature in the second heat treatment step can be lower than that in the first heat treatment step, as long as the phthalocyanine is sublimated in the second heat treatment step. In other words, it is preferable that the calcination temperature in the first heat treatment step is higher than that in the second heat treatment step.

[0051] The calcination time in the first heat treatment step is preferably 40 to 80 minutes. When the first nitrogen-containing transition metal complex 11 is iron phthalocyanine, the first heat treatment step is a step of sublimating the iron phthalocyanine and agglomerating Fe. If the calcination time in the first heat treatment step is short, the raw material iron phthalocyanine may remain as a raw material and increase instability. If the calcination time is long, the aggregation of Fe proceeds too much, reducing the surface area of ​​the shell layer formed on the core, and reducing the reactive active sites.

[0052] On the other hand, the second heat treatment step is a step of forming a carbon thin film on the aggregated Fe, and the calcination time is preferably 40 to 80 minutes, more preferably 40 to 60 minutes. The calcination time in the second heat treatment step can be shorter than the calcination time in the first heat treatment step. That is, the calcination time in the first heat treatment step is preferably longer than the calcination time in the second heat treatment step. If the calcination time in the second heat treatment step is too short, there is a problem that the raw material iron phthalocyanine remains as a raw material and instability increases. In addition, if the calcination time is long, there is a problem that the aggregation proceeds too much, and the reaction active points decrease.

[0053] The method may further include a step of lowering the temperature between the first heat treatment step and the second heat treatment step. It is preferable that the first heat treatment step and the second heat treatment step are not performed consecutively. By including a step of lowering the temperature between the first heat treatment step and the second heat treatment step, it is possible to prevent the iron phthalocyanine introduced in the second heat treatment step from being decomposed at high temperature.

[0054] Therefore, in the method for producing a catalyst according to the present disclosure, a temperature lowering step is provided between the first heat treatment step and the second heat treatment step. The temperature range in this temperature lowering step is preferably set to a temperature below which the second nitrogen-containing transition metal complex does not decompose.

[0055] If the second heat treatment step is performed at a temperature higher than the temperature at which the second nitrogen-containing transition metal complex decomposes, the second nitrogen-containing transition metal complex decomposes and the shell is not formed. Even if the second heat treatment step is performed at a temperature at which the second nitrogen-containing transition metal complex does not decompose, for example, if the step is performed to lower the temperature to less than 30° C., the catalyst production cost increases, which is not preferable.

[0056] (Carbon materials) The weight of the second nitrogen-containing transition metal complex in the second heat treatment step relative to the carbon material obtained in the first heat treatment step is preferably greater than the weight of the first nitrogen-containing transition metal complex relative to the carbon material in the first heat treatment step. Therefore, the amount of iron phthalocyanine added in the second heat treatment step is preferably greater than the amount of iron phthalocyanine added in the first heat treatment step. The reason why the amount of iron phthalocyanine added in the second heat treatment step is greater is to allow the Fe aggregated in the first heat treatment step to be sufficiently covered with a carbon thin film in the second heat treatment step.

[0057] Furthermore, the weight ratio of the first nitrogen-containing transition metal complex to the carbon material in the first heat treatment step is preferably 0.01 to 100. Moreover, the weight ratio of the second nitrogen-containing transition metal complex to the carbon material obtained in the first heat treatment step in the second heat treatment step is preferably 0.1 to 100.

[0058] If the weight ratio of the first nitrogen-containing transition metal complex to the carbon material in the first heat treatment step is less than 0.01, the amount of cores (aggregated Fe) formed will be small. If the weight ratio is more than 100, the aggregation of Fe will proceed too much, reducing the surface area of ​​the shell layer formed on Fe and decreasing the reactive active sites.

[0059] If the weight ratio of the second nitrogen-containing transition metal complex to the carbon material obtained in the first heat treatment step in the second heat treatment step is less than 0.1, the shell layer (carbon thin film) may not be sufficiently formed on the core. If the weight ratio is more than 100, the aggregation proceeds too much, and the reaction active sites decrease.

[0060] Examples of such carbon materials include a sheet-like body (or plate-like body) containing carbon fibers such as carbon paper, and carbon powder such as carbon black. An example of a case where carbon paper is used as the carbon material is TGP, which will be described later (see Example 1). In this case, the weight ratio of the first nitrogen-containing transition metal complex to the carbon material in the first heat treatment step is 0.1, and the weight ratio of the second nitrogen-containing transition metal complex to the carbon material obtained in the first heat treatment step in the second heat treatment step is 40, which is within the range of the weight ratio.

[0061] The advantage of using carbon paper as the carbon material is that the obtained sample can be made into an electrode without processing it. In addition, if the carbon material is carbon paper, it is easy to laminate, and the obtained sample can be laminated and adjusted according to the required output.

[0062] When carbon powder such as carbon black is used as the carbon material, the specific surface area of ​​the carbon fiber sheet such as carbon paper is 0.1 to 10 m 2 / g, while the specific surface area of ​​carbon powder is 100-1000 m 2 / g. Therefore, the weight of the first nitrogen-containing transition metal complex and the second nitrogen-containing transition metal complex when carbon powder is used is 10 to 100 times larger than when a carbon fiber sheet such as carbon paper is used.

[0063] The advantage of using carbon black as the carbon material is that it has an overwhelmingly larger specific surface area than carbon paper, allowing it to support a large amount of the catalyst. As a result, when an electrode is made, the amount of catalyst per unit area (or volume) of the electrode is overwhelmingly larger than when the carbon material is carbon paper, improving the battery performance.

[0064] Furthermore, when the carbon material is carbon powder such as carbon black, it can be mixed with a binder (typically PTFE) and made into an electrode (air electrode) by coating or rolling.

[0065] When the carbon material is carbon fiber such as carbon paper, the weight ratio in the first heat treatment step is in the range of 0.01 to 1.0, and the weight ratio in the second heat treatment step is in the range of 0.1 to 50.0. When the carbon material is carbon powder such as carbon black, the weight ratio in the first heat treatment step is in the range of 0.1 to 100, and the weight ratio in the second heat treatment step is in the range of 1 to 100.

[0066] (catalyst) 5, the production method according to the first embodiment provides a catalyst 1 having a carbon material 12, a metal-containing core (fine particle) 13 supported on the surface of the carbon material 12, and a shell layer 15 covering the surface of the core 13. As shown in FIG 6, as a modified example, the catalyst 1 may have a configuration in which the shell layer 15 covers both the surface of the core 13 and the surface of the carbon material 12.

[0067] In the catalyst 1, the core 13 is a fine particle containing a metal. The metal contained in the core 13 includes at least a first transition metal. Examples of the first transition metal include Fe (iron) and Co (cobalt). The shell layer 15 preferably includes a second metal, C (carbon), and N (nitrogen). The surface of the shell layer 15 is preferably composed of Fe, N, and C.

[0068] More preferably, the first transition metal is at least one metal selected from Fe or Co, and Fe is particularly preferred. The core 13 preferably further contains carbon, more preferably Fe3C. This provides a thermodynamically stable structure. The shell layer 15 preferably contains at least one second transition metal selected from Fe or Co. Furthermore, the shell layer 15 is preferably an amorphous layer. A method for identifying Fe3C contained in the core 13 includes, for example, a method for measuring an EXAFS (Extended X-ray Absorption Fine Structure) spectrum of the carbon material containing the core 13 obtained in the first post-heat treatment step, and confirming the presence or absence of a peak derived from Fe3C. A method for identifying that the shell layer 15 is an amorphous layer includes, for example, a method for measuring a Raman spectrum of the carbon material containing the shell layer 15 on the surface obtained in the second heat treatment step, and confirming the presence or absence of a peak derived from amorphous carbon.

[0069] (air electrode) The obtained catalyst 1 can be used for the air electrode of an air battery. That is, the air electrode contains the catalyst 1 and at least a conductive material to be made into an electrode. When the carbon material 12 constituting the catalyst 1 is a sheet-like carbon fiber such as carbon paper, one or more sheets of the catalyst 1 can be stacked to make an electrode (air electrode). When the carbon material is carbon powder such as carbon black, the catalyst 1 can be mixed with a binder (typically PTFE) and applied or rolled to make an electrode (air electrode). [Embodiment 2] In the above-mentioned catalyst manufacturing method, an example of using a sheet or plate-like body such as carbon paper containing carbon fiber and an example of using carbon powder such as carbon black are shown. The carbon material used in the catalyst manufacturing method of the present disclosure is not necessarily limited to a sheet or plate-like body, and may be, for example, particulate.

[0070] Fig. 7 is an explanatory diagram showing a catalyst 10 produced by the production method of a catalyst according to embodiment 2, and Fig. 8 is an explanatory diagram showing a modified example thereof. In the production method according to embodiment 2, the carbon material 16 has a different structure from that of embodiment 1, but the treatments in each step are the same.

[0071] In the first heat treatment step (S1), the carbon material 16 heated together with the first nitrogen-containing transition metal complex is in the form of particles as shown in FIG. 7. In the first heat treatment step, cores 13 of particles (iron-containing particles) containing mainly Fe as the central metal of the first nitrogen-containing transition metal are formed (aggregated Fe, core formation) on the surface of the particulate carbon material 16. Then, after a step of lowering the temperature, in the second heat treatment step (S2), the carbon material 16 having the cores 13 and the second nitrogen-containing transition metal complex are heated in a second inert gas atmosphere. As a result, a shell layer 17 is formed on the surface of the cores 13, and a catalyst 10 is obtained through an acid washing step (S3).

[0072] 7, in the catalyst 10 according to the second embodiment, a core 13 having a shell layer 17 is attached to the surface of a particulate carbon material 16. The particle diameter of the particulate carbon material 16 is larger than the particle diameter of the core 13 and is also larger than the overall diameter of the core 13 including the shell layer 17.

[0073] 8, in the second heat treatment step (S2), the shell layer 17 may be formed so as to cover both the surface of the core 13 and the surface of the carbon material 16. In this manner, as a modified example, the catalyst 10 according to the second embodiment may be formed so that the shell layer 17 covers both the surface of the core 13 and the surface of the carbon material 16.

[0074] The obtained catalyst 10 can be used for the air electrode of an air battery. For example, the catalyst 10, a binder, and a conductive assistant are mixed to prepare a paste, which is then applied to a collector electrode to form an air electrode.

[0075] Example 1 A method for producing a catalyst according to the present disclosure and Example 1 of a catalyst (carbon catalyst) produced by the method will be described together with the results of a verification experiment.

[0076] (material) Graphite carbon paper (TGP-H-090 (hereinafter referred to as TGP), manufactured by Toray Industries, Inc.) was used as the carbon material to be subjected to the first heat treatment step. Iron phthalocyanine (FePc, manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the first nitrogen-containing transition metal complex and the second nitrogen-containing transition metal complex.

[0077] (Process A: Transition metal-containing particle formation process (first heat treatment process)) In the first heat treatment step, 10 mg of iron phthalocyanine and 1 cm 2 TGP 8 sheets (1cm 2 =12.5mg / 1 sheet) and 15cm 3 The sample was placed in a crucible, covered, and heated at 5°C / min in an Ar atmosphere, then heat-treated at a firing temperature of 1000°C for 1 hour. In the first heat treatment step, Fe-containing particles are produced by sublimation of iron phthalocyanine, precipitation on the carbon fiber in the TGP, and thermal decomposition, and Fe is uniformly dispersed on the carbon fiber surface in the TGP. The obtained sample is called TGP-10CFePc1000B.

[0078] (Process B: Transition metal-containing carbon thin film formation process) (Second heat treatment process) In the second heat treatment step, 1000 mg of iron phthalocyanine and two sheets of the sample (TGP-10CFePc1000B) obtained in treatment A were placed on a 15 cm 3 The mixture was placed in a crucible, covered, and heated at 1°C / min in an Ar atmosphere, and then heat-treated for 1 hour at a firing temperature of 1000°C. In the second heat treatment step, an Fe-containing carbon thin film was produced by sublimation, precipitation, and thermal decomposition of iron phthalocyanine.

[0079] (Acid washing process) The carbon material after the second heat treatment step was washed with 6M HCl (acid washing) to remove the Fe species not covered with the shell layer, and then dried in vacuum.

[0080] A series of transition metal-containing carbon thin film formation processes including the second heat treatment step and the acid washing step is referred to as Process B, and the obtained sample is referred to as TGP-10CFePc1000-1000CFePc1000.

[0081] Comparative Example 1 For comparison in the verification experiment described later, a sample was also prepared as Comparative Example 1 in which the carbon material TGP was subjected to treatment A and acid washing without treatment B. This sample was designated TGP-10CFePc1000.

[0082] (Verification experiment results) As a verification experiment for the samples produced in the present embodiment 1, currents were measured during an oxygen evolution reaction and an oxygen reduction reaction. In the following verification experiment, sample TGP-10CFePc1000 is referred to as Comparative Example 1, and sample TGP-10CFePc1000-1000CFePc1000 is referred to as Example 1.

[0083] Table 1 shows the samples in Example 1 and Comparative Example 1, and whether or not they were subjected to treatment A and treatment B. In the present embodiment 1, experiments were also carried out in the case where a Pt plate was used as a catalyst in Reference Example 1, and an Ir wire was used as a catalyst in Reference Example 2.

[0084] [Table 1]

[0085] In Example 1 and Comparative Example 1, a Ni wire was tied to the obtained carbon paper sample to form a lead, which served as a working electrode. For the Pt plate in Reference Example 1, a fluororesin adhesive tape (Nitoflon, manufactured by Nitto Denko) was used to mask the plate to form an electrode with a diameter of 6 mm, which served as a working electrode. For the Ir wire in Reference Example 2, a fluororesin adhesive tape (Nitoflon, manufactured by Nitto Denko) was used to mask the plate to form an electrode with a diameter of 0.5 mm and a length of 1 cm, which served as a working electrode. A Pt wire was used as the counter electrode, and a Hg / HgO electrode was used as the reference electrode. A 1M KOH aqueous solution was placed in a Teflon (registered trademark) container to form a three-electrode cell, and electrochemical measurements were performed using an electrochemical measurement device (ALS, 660B).

[0086] The KOH aqueous solution of the electrolyte was prepared from KOH (Alfa Aesar (registered trademark), 99.99%) using ultrapure water obtained from an ultrapure water production apparatus (Barnstead, D7403). The electrolyte temperature was 25°C.

[0087] As a pretreatment, potential scanning was performed in an Ar atmosphere in the range of -0.9V to 0.3V at 50mV / s for 10 cycles, and then potential scanning was performed from -0.9V to 0.3V at 10mV / s to measure the background current of the oxygen reduction reaction. The oxygen reduction current and oxygen evolution current were measured in an O2 atmosphere. The oxygen reduction current was measured from -0.9V to 0.3V, and the oxygen evolution current was measured from 0.3V to 0.8V while potential scanning was performed at 10mV / s.

[0088] FIG. 9 shows the relationship between oxygen reduction current and electrode potential. The oxygen reduction current is the current measured in an O2 atmosphere minus the background current, and the sign of the reduction current is negative. Comparing Example 1, in which both iron-containing particle formation (treatment A) and iron-containing carbon thin film formation (treatment B) were performed on TGP, with Comparative Example 1, in which iron-containing particle formation (treatment A) was performed on TGP, a reduction in overvoltage of 150 mV was observed, and it was confirmed that the peak current was also greatly improved. That is, in Example 1, a significant promotion of oxygen reduction activity was achieved.

[0089] In addition, when comparing Example 1 and Reference Example 1 (Pt plate), the peak current value of Example 1 is lower, but it is −0.4 mA / cm 2 Since the overpotential is low up to 1000 kV, it can be said that the catalyst of Example 1 may be superior to the Pt plate catalyst for operation at low current densities.

[0090] FIG. 10 shows the relationship between oxygen generating current and electrode potential. In this experimental result, an increase in oxygen generating current was confirmed when Comparative Example 1 was compared with Reference Example 2. By only applying Treatment A, the catalyst showed better performance than an Ir wire catalyst. Furthermore, when Example 1, in which both iron-containing particle formation (Treatment A) and iron-containing carbon thin film formation (Treatment B) were applied to TGP, were compared with Comparative Example 1, in which iron-containing particle formation (Treatment A) was applied to TGP, a reduction in overvoltage of 200 mV was observed, and it was confirmed that the current at high potential was also improved. That is, a significant promotion of oxygen generating activity was achieved in Example 1.

[0091] Example 2 A method for producing a catalyst according to the present disclosure and Example 2 of a catalyst (carbon catalyst) produced by the method will be described together with the results of a verification experiment.

[0092] (material) Graphite carbon paper (TGP-H-090 (TGP), manufactured by Toray Industries, Inc.) was used as the carbon material subjected to the first heat treatment step. Iron phthalocyanine (FePc, manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the first nitrogen-containing transition metal complex and the second nitrogen-containing transition metal complex. These materials were the same as those in Example 1.

[0093] (Treatment C: Transition metal-containing particle formation step (first heat treatment step)) The first heat treatment step of treatment C was the same as the first heat treatment step of treatment A in Example 1. That is, 10 mg of iron phthalocyanine and 1 cm 2 8 sheets of TGP (1cm2 = 12.5mg / sheet) and 15cm 3 The sample was placed in a crucible, covered, and heated at 5°C / min in an Ar atmosphere, then heat-treated at a firing temperature of 1000°C for 1 hour. In the first heat treatment step, Fe-containing particles are produced by sublimation of iron phthalocyanine, precipitation on the carbon fiber in the TGP, and thermal decomposition, and Fe is uniformly dispersed on the carbon fiber surface in the TGP. The obtained sample is called TGP-10CFePc1000B.

[0094] (Process D: Transition metal-containing carbon thin film formation process) (Second heat treatment process) In the treatment D, the amount of iron phthalocyanine used in the second heat treatment step was different from that in the treatment B of Example 1. That is, in the second heat treatment step, 100 mg of iron phthalocyanine and one sheet of the sample (TGP-10CFePc1000B) obtained in the treatment C were heated to 15 cm 3 The mixture was placed in a crucible, covered with a lid, and then heated at 1°C / min in an Ar atmosphere, followed by heat treatment at 1000°C for 1 hour. In the second heat treatment step, the iron phthalocyanine was sublimated and precipitated and thermally decomposed to produce an Fe-containing carbon thin film.

[0095] (Acid washing process) The carbon material after the second heat treatment step was washed with 6M HCl (acid washing) to remove the Fe species not covered with the shell layer, and then dried in vacuum.

[0096] This series of transition metal-containing carbon thin film formation processes including the second heat treatment step and the acid washing step is referred to as Process D, and the obtained sample is referred to as TGP-10CFePc1000-100CFePc1000.

[0097] Comparative Example 2 For comparison in the verification experiment described later, a sample was also prepared as Comparative Example 2 in which 100 mg of iron phthalocyanine was used in Treatment C and 100 mg of iron phthalocyanine was used in Treatment D relative to the carbon material TGP. This sample was designated TGP-100CFePc1000-100CFePc1000.

[0098] (Verification experiment results) As a verification experiment for the sample produced in Example 2, the current during the oxygen evolution reaction and the oxygen reduction reaction were measured. In the following verification experiment, sample TGP-100CFePc1000-100CFePc1000 is referred to as Comparative Example 2, and sample TGP-10CFePc1000-100CFePc1000 is referred to as Example 2.

[0099] Table 2 shows the samples in Comparative Example 2 and Example 2, and whether or not they underwent treatment C and treatment D. In the present embodiment 2, experiments were also conducted in the case where a Pt plate was used as a catalyst in Reference Example 1, and an Ir wire was used as a catalyst in Reference Example 2.

[0100] [Table 2]

[0101] In Example 2 and Comparative Example 2, a Ni wire was tied to the obtained carbon paper sample to form a lead, which served as a working electrode. For the Pt plate in Reference Example 1, a fluororesin adhesive tape (Nitoflon, manufactured by Nitto Denko) was used for masking to form an electrode with a diameter of 6 mm, which served as a working electrode. For the Ir wire in Reference Example 2, a fluororesin adhesive tape (Nitoflon, manufactured by Nitto Denko) was used for masking to form an electrode with a diameter of 0.5 mm and a length of 1 cm, which served as a working electrode. A Pt wire was used as the counter electrode, and a Hg / HgO electrode was used as the reference electrode. A 1M KOH aqueous solution was placed in a Teflon (registered trademark) container to form a three-electrode cell, and electrochemical measurements were performed using an electrochemical measurement device (ALS, 660B).

[0102] The KOH aqueous solution of the electrolyte was prepared from KOH (Alfa Aesar (registered trademark), 99.99%) using ultrapure water obtained from an ultrapure water production apparatus (Barnstead, D7403). The electrolyte temperature was 25°C.

[0103] As a pretreatment, potential scanning was performed 10 cycles at 50 mV / s in the range of -0.9 V to 0.3 V in an Ar atmosphere, and then potential scanning was performed at 10 mV / s from -0.9 V to 0.3 V to measure the background current of the oxygen reduction reaction. The oxygen reduction current and oxygen evolution current were measured in an O2 atmosphere. The oxygen reduction current was measured from -0.9 V to 0.3 V, and the oxygen evolution current was measured from 0.3 V to 0.8 V while potential scanning was performed at 10 mV / s.

[0104] As shown in the relationship between oxygen reduction current and electrode potential in Fig. 9, in Example 2, in which both treatments C and D were performed and the weight of iron phthalocyanine in treatment D was greater than that in treatment C, a reduction in overvoltage of 50 mV was confirmed compared to Comparative Example 2. That is, in Example 2, in which the weight of iron phthalocyanine in treatment D was greater than that in treatment C, promotion of oxygen reduction activity was achieved. Note that, when Example 2 is compared with Reference Example 1 (Pt plate), the peak current value in Example 2 was lower, but it was -0.3 mA / cm 2 Since the overpotentials are almost the same up to this point, it can be said that the catalyst of Example 2 has the potential to rival the Pt plate catalyst in terms of operation at low current densities.

[0105] 10 shows the relationship between oxygen generating current and electrode potential, and in Example 2, in which both treatments C and D were performed and the weight of iron phthalocyanine in treatment D was greater than that in treatment C, an increase in oxygen generating current was confirmed compared to Comparative Example 2. In addition, when Example 2 was compared with Reference Example 2, a reduction in overvoltage of 200 mV was observed, and it was confirmed that the peak current was also improved. That is, in Example 2, a greater promotion of oxygen generating activity was achieved than in the case of the Ir wire catalyst.

[0106] As described above, the method for producing a catalyst according to the present disclosure makes it possible to produce a catalyst having excellent catalytic ability for both oxygen reduction and oxygen generation without using a precious metal such as platinum. By applying the catalyst having catalytic ability for both oxygen reduction and oxygen generation obtained in this way to an air electrode, it becomes possible to improve the battery characteristics of an air battery. Furthermore, by applying an air electrode containing a catalyst according to the present disclosure to a metal-air battery, the oxygen reduction reaction can be further activated at the air electrode. By using an air electrode containing a catalyst according to the present disclosure as a positive electrode during charging in a metal-air secondary battery, the catalyst used in the air electrode can be provided with sufficient functions as an oxygen reduction catalyst required during discharge and an oxygen generation catalyst required during charging.

[0107] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. [Explanation of symbols]

[0108] 1, 10 Catalyst 11 The first nitrogen-containing transition metal complex 12, 16 Carbon materials 13 cores 14. Second nitrogen-containing transition metal complex 15, 17 Shell layer

Claims

1. A carbon material; fine particles containing a metal supported on a surface of the carbon material; a shell layer covering the surface of the fine particles, A method for producing a catalyst that functions as an oxygen reduction catalyst and / or an oxygen evolution catalyst when used in an air electrode of a battery, comprising the steps of: a first heat treatment step of heating the carbon material and the first nitrogen-containing transition metal complex in a first inert gas atmosphere to form the fine particles; a second heat treatment step of heating the carbon material that has been subjected to the first heat treatment step and a second nitrogen-containing transition metal complex in a second inert gas atmosphere to form the shell layer; the first nitrogen-containing transition metal complex and the second nitrogen-containing transition metal complex are iron phthalocyanines having Fe as a central metal, The firing temperature in the first heat treatment step is 800 to 1200° C., and the firing temperature in the second heat treatment step is 600 to 1200° C., a weight of the second nitrogen-containing transition metal complex relative to the carbon material that has undergone the first heat treatment step is greater than a weight of the first nitrogen-containing transition metal complex relative to the carbon material in the first heat treatment step.

2. The method for producing the catalyst according to claim 1, The method for producing a catalyst, further comprising an acid washing step after the second heat treatment step.

3. The method for producing the catalyst according to claim 1 or 2, A method for producing a catalyst, wherein the calcination temperature in the first heat treatment step is higher than the calcination temperature in the second heat treatment step.

4. In the method for producing the catalyst according to any one of claims 1 to 3, The firing time in the first heat treatment step is 40 to 80 minutes, and the firing time in the second heat treatment step is 40 to 80 minutes; A method for producing a catalyst, wherein a calcination time in the first heat treatment step is longer than a calcination time in the second heat treatment step.

5. In the method for producing the catalyst according to any one of claims 1 to 4, A method for producing a catalyst, further comprising a step of lowering a temperature between the first heat treatment step and the second heat treatment step.

6. In the method for producing the catalyst according to any one of claims 1 to 5, a weight ratio of the first nitrogen-containing transition metal complex to the carbon material in the first heat treatment step is 0.01 to 100; A method for producing a catalyst, wherein a weight ratio of the second nitrogen-containing transition metal complex in the second heat treatment step to the carbon material that has been subjected to the first heat treatment step is 0.1 to 100.

7. In the method for producing the catalyst according to any one of claims 1 to 6, The method for producing a catalyst, wherein the carbon material used in the first heat treatment step is carbon paper.

8. In the method for producing the catalyst according to any one of claims 1 to 6, The method for producing a catalyst, wherein the carbon material used in the first heat treatment step is carbon black.

Citation Information

Patent Citations

  • Manufacturing method of electrocatalyst for fuel cell, electrocatalyst manufactured by its method, as well as fuel cell using that electrocatalyst

    JP2007026746A

  • Modified material, electrode catalyst for fuel cell, membrane-electrode assembly, and fuel cell

    JP2012110811A

  • Method of manufacturing carbon catalyst and fuel cell using the catalyst

    JP2013158674A

  • Carbon catalyst, method for producing carbon catalyst, catalyst ink using carbon catalyst, and fuel cell

    JP2014028360A

  • Novel non-platinum metal catalyst material

    JP2016527075A